Improvement of flux pinning in GdBa2Cu3O7−δ thin film by nanoscale ferromagnetic La0.67Sr0.33MnO3 pretreatment of substrate surface. Issue 1 (January 2018) - Wang, Ying; Li, Yijie; Liu, Linfei; Xu, Da
Abstract: The present paper presents the effects of ferromagnetic La0.67 Sr0.33 MnO3 (LSMO) nanoparticles on the pinning characteristics of an epitaxial GdBa2 Cu3 O7−δ ((Gd) BCO) film deposited on top. LSMO nanoparticles with the size between 10 and 20 nm were obtained on a (001) STO substrate by RF sputtering method. The analyses of magnetic measurements revealed that the presence of a complex vortex pinning mechanism within the (Gd) BCO film deposited on the undecorated substrate. With respect to a reference (Gd) BCO film, two additional pinning effects in LSMO decorated (Gd) BCO film were observed. One is the effect of the threading dislocations due to LSMO nanoparticles, and the other one is the LSMO nanoparticles itself. Like other nanosized particles, the LSMO nanoparticles on substrate will induce threading dislocations passing through the (Gd) BCO film. These threading dislocations serve as correlated pinning centers along the c-axis, which lead to the improvement of flux pinning properties in LSMO decorated (Gd) BCO film. According to the ferromagnetic property of LSMO material, a magnetic pinning mechanism was proposed to explain the significant increase of Jc and Fp values. The flux pinning abilities of LSMO nanoparticles were evaluated. The enhanced pinning characteristics in the high field region and high temperature together with the movement of HFpmax (the corresponding field of Fpmax) also suggest a magnetic pinning mechanism for LSMO nanoparticles existed in LSMO decorated (Gd) BCO film.